The Kingdom of Siak a Symbol of Islamic Civilization in East Riau - Santika , Mira; Roza, Ellya (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2023)
The purpose of writing this article is to explore information about the Siak Kingdom as a symbol of Islamic civilization in eastern Riau. This research uses the library research method or also called the library method where researchers use various literature to obtain information, and use a qualitative approach because the data produced is in the form of words or descriptions. Based on the results of research, Siak Kingdom has high historical and cultural value. This kingdom has unique architectural characteristics and is a place of social and cultural activities for the surrounding community. The Kingdom of Siak is also the center of cultural activities, and many great scholars and famous Islamic figures in Indonesia have visited the Kingdom of Siak. The Kingdom of Siak is also the center of cultural activities, and many great scholars and famous Islamic figures in Indonesia have visited the Kingdom of Siak. Every year, this mosque becomes a religious tourism destination for Indonesians who want to take part in traditional celebrations. With the existence of various buildings as historical relics and civilization of the Siak Kingdom, it can be said that the Siak Kingdom is a symbol of Islamic civilization in eastern Riau. These relics include Siak Palace, Syahabuddin Mosque, High Density Hall. Balairung Sri, royal crown, stump cannon, Koto Tinggi sultan tomb complex, Heroes Monument. In the end, this study recommends that the government and society should maintain and preserve various cultural heritage buildings as valuable cultural heritage for the Indonesian nation